THE INFLUENCE OF COMPENSATION, WORK ENVIRONMENT, AND EXTRINSIC MOTIVATION ON TEACHER JOB SATISFACTION - Pratama, Aldo Syahril Muda; Mulyono, Agus (PT. Antis International Publisher, 2024)
Teachers as human resources have a very important role in achieving the goals of educational institutions. Paying attention to teacher job satisfaction is an important step to improve the quality of education and ensure their welfare. Therefore, in-depth research is needed on the factors that influence teacher job satisfaction, as a basis for evaluating management policies and practices in educational institutions. This paper presents a study of the influence of compensation, work environment, and extrinsic motivation on teacher job satisfaction at the Roudlotul Jannah Education Foundation. This research is a type of quantitative research. The subjects in this research were teachers at the Roudlotul Jannah Education Foundation. The technique used in sampling was a saturated sampling technique with a total of 46 respondents. The method used in analyzing is multiple linear regression. The results of the research show that the compensation variable has a significant positive effect on teacher job satisfaction with a value of t count 6,077 > t-table 1,681952, the work environment variable has a significant positive effect on teacher job satisfaction with a value of t count 2,653 > t-table 1,681952, then the extrinsic motivation variable has a significant positive effect on teacher job satisfaction with a calculated t value 2,125 > t-table 1,681952, while the variables of compensation, work environment, and extrinsic motivation simultaneously have a significant positive effect on teacher job satisfaction at the Roudlotul Jannah Education Foundation.